PERSEPSI IBU DALAM PEMENUHAN GIZI BALITA DI KELURAHAN SEI SERINDAN TAHUN 2018 - KASMINAH .; ERLINA ESTHER (LP2MTBM MAKARIOZ, 2019)
Nutrition is one determinant of the quality of human resources. Malnutrition will cause the failure of physical growth and intellectual development, lowers labor productivity and lowered immune system, resulting in increase morbidity and mortality. The purpose of this study was to describe the perception of mother in nutrition status of children under five with malnutrition in villages Tano Bato Padangsidimpuan districts north of the city Padangsidimpuan. This study used a qualitative approach which is defined as research that produces descriptive data in the form of interviews with informants. Informants in this research that mothers who have children with malnutrition status. Data collection method is the in-depth interview is to do a question and answer with the informant.The results showed that all respondents have a positive perception about nutrition and MP-ASI (PMT), also already know the function of diet and balanced diet among children under five. Whereas nutritional requirements, nutritional status and some portions of food appropriate to the age of children under five is not yet known by all informants. Community health centers should need to increase effective extension to increase public knowledge about nutrition especially mothers of children under five in order toddler avoid malnutrition and to achieve optimal health status.